THE INFLUENCE OF RELIGIOSITY AND COMMITMENT ON THE PERFORMANCE OF EDUCATION PERSONNEL AT THE DAAR EL-QOLAM 1 GINTUNG JAYANTI TANGERANG ISLAMIC BOARDING SCHOOL - Indah Lestari; Fitri Aini Azhari; Furniawan (Universitas La Tansa Mashiro, 2023)
The aim of this research is to determine the influence of religiosity on the performance of educational staff at the Daar El-Qolam 1 Gintung Jayanti Tangerang Islamic Boarding School, and to determine the effect of commitment on the performance of educational staff at the Daar El-Qolam 1 Gintung Jayanti Islamic Boarding School, Tangerang, both partially and simultaneously. This research method is a quantitative descriptive approach. The research population was all educational staff at Daar El Qolam Islamic Boarding School 1 Gitung, Jayanti, Tangerang, totaling 42 educational staff. Using a saturated sample by taking all the educational staff at the Daar El-Qolam 1 Gintung Jayanti Tangerang Islamic Boarding School. And the analysis technique used in this research is multiple regression testing. The results of the study concluded that H1 was accepted, which means that the religiosity variable (X1) has a positive and significant influence on the performance of educational staff (Y) in educational staff at the Daar el-Qolam 1 Gintung Jayanti Tangerang Islamic Boarding School. In the commitment variable (X2) there is a positive and significant influence on the performance of educational staff (Y) in educational staff at the Daar el-Qolam 1 Gintung Jayanti Tangerang Islamic Boarding School. In the variables religiosity (X1) and commitment (X2) there is a positive and significant influence on the performance of educational staff (Y) at the Daar El-Qolam 1 Gintung Jayanti Tangerang Islamic Boarding School.